2014
DOI: 10.12988/ija.2014.416
|View full text |Cite
|
Sign up to set email alerts
|

Some new inequalities on geometric multiplicities and Gersgorin discs

Abstract: In this paper the authors continue their work on geometric multiplicities and Geršgorin discs done in a series of four recent papers. The new results involve principal submatrices, an upper bound on the absolute value of an eigenvalue, the rank of a matrix, non-real eigenvalues, and powers of matrices. Some consequences of the results and examples are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Varga's nice book [31] surveys various applications and extensions of this important theorem. Recently, Marsli and Hall [25] found an interesting result, which states that if λ is an eigenvalue of an n × n matrix A with geometric multiplicity k, then λ is in at least k of the n Gerŝgorin discs of A. Fiedler et al [12] proved that for a triple of positive integers k, r, t with k ≤ r ≤ t, there is a t × t complex matrix A and an eigenvalue λ of A such that λ has geometric multiplicity k and algebraic multiplicity t, and λ is in precisely r Gerŝgorin discs of A. Marsli and Hall extended these results in subsequent papers [24,26,27]. Bárány and Solymosi [6] showed that if the matrix entries are non-negative and an eigenvalue has geometric multiplicity at least two, then this eigenvalue lies in a smaller disk.…”
mentioning
confidence: 92%
“…Varga's nice book [31] surveys various applications and extensions of this important theorem. Recently, Marsli and Hall [25] found an interesting result, which states that if λ is an eigenvalue of an n × n matrix A with geometric multiplicity k, then λ is in at least k of the n Gerŝgorin discs of A. Fiedler et al [12] proved that for a triple of positive integers k, r, t with k ≤ r ≤ t, there is a t × t complex matrix A and an eigenvalue λ of A such that λ has geometric multiplicity k and algebraic multiplicity t, and λ is in precisely r Gerŝgorin discs of A. Marsli and Hall extended these results in subsequent papers [24,26,27]. Bárány and Solymosi [6] showed that if the matrix entries are non-negative and an eigenvalue has geometric multiplicity at least two, then this eigenvalue lies in a smaller disk.…”
mentioning
confidence: 92%
“…An interesting and recent theorem of Marsli and Hall [5] states that if an eigenvalue of a matrix A has geometric multiplicity k, then it lies in at least k of the Gershgorin disks of A. They have extended this result in subsequent papers [3,6,7,8]. Here we focus on the k = 2 case for non-negative matrices.…”
Section: Introduction and Main Resultsmentioning
confidence: 97%